Screening of anti-inflammatory activities components of Angelica dahurica root based on spectrum-effect relationship analysis and NF-κB pathway - Huan Shi; Qianqian Wang; Yaqing Chang; Yuguang Zheng; Dan Zhang; Yunsheng Zhao; Long Guo (Frontiers Media S.A., 2024)
Angelica dahurica root (ADR), a commonly utilized herbal medicine in China and other Asian nations, which has anti-inflammatory effects on diverse inflammatory ailments. However, the bioactive components and underlying mechanism responsible for the anti-inflammatory effect of ADR are still unclear. This work attempted to discover the anti-inflammatory bioactive compounds and explore their underlying mechanism in ADR based on spectrum-effect relationship analysis and NF-κB signaling pathway. Chromatographic fingerprints of ADR samples were established by high performance liquid chromatography with diode array detection (HPLC-DAD), and a total of eleven common peaks were selected. Then, high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (HPLC-Q/TOF-MS) was employed for identification of eleven common peaks in ADR Meanwhile, the anti-inflammatory activities of ADR samples were assessed by inhibition of NO, interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) production in LPS-induced RAW264.7 cells. The spectrum-effect relationships between the eleven common peaks in HPLC fingerprints and anti-inflammatory effects of ADR samples were investigated to identify the potential anti-inflammatory bioactive compounds by grey relational analysis (GRA) and partial least squares regression (PLSR). The spectrum-effect relationship analysis results indicated that six coumarin compounds, including bergapten, xanthotoxin, phellopterin, isoimperatorin, xanthotoxol and imperatorin could be potential anti-inflammatory bioactive compounds in ADR. The further validation experiments also showed that these six coumarins demonstrated significant inhibition of NO, IL-1β, IL-6, and TNF-α production in LPS-induced RAW264.7 cells. In addition, western blot analysis was conducted to explore the mechanisms of two potential anti-inflammatory bioactive compounds (phellopterin and isoimperatorin) by assessing the protein levels in the NF-κB signaling pathway. The western blot results illustrated that phellopterin and isoimperatorin could significantly down-regulate the phosphorylated NF-κB p65 (p-p65), phosphorylated IκBα (p-IκBα) and iNOS, and depress the pro-portion of p-p65/p65 and p-IκBα/IκBα, which indicated that these two coumarins in ADR could potentially exert anti-inflammatory effects by suppressing of NF-κB pathway.